"Late-onset" ADHD symptoms in young adulthood: Is this ADHD?. Issue 10 (August 2022) - Riglin, Lucy; Wootton, Robyn E.; Livingston, Lucy A.; Agnew-Blais, Jessica; Arseneault, Louise; Blakey, Rachel; Agha, Sharifah Shameem; Langley, Kate; Collishaw, Stephan; O'Donovan, Michael C.; Davey Smith, George; Stergiakouli, Evie; et al.
Objective: We investigated whether "late-onset" ADHD that emerges in adolescence/adulthood is similar in risk factor profile to: (1) child-onset ADHD, but emerges later because of scaffolding/compensation from childhood resources; and (2) depression, because it typically onsets in adolescence/adulthood and shows symptom and genetic overlaps with ADHD.Methods: We examined associations between late-onset ADHD and ADHD risk factors, cognitive tasks, childhood resources and depression risk factors in a population-based cohort followed-up to age 25 years ( N =4224–9764).Results: Parent-rated late-onset ADHD was like child-onset persistent ADHD in associations with ADHD polygenic risk scores and cognitive task performance, although self-rated late-onset ADHD was not. Late-onset ADHD was associated with higher levels of childhood resources than child-onset ADHD and did not show strong evidence of association with depression risk factors.Conclusions: Late-onset ADHD shares characteristics with child-onset ADHD when parent-rated, but differences for self-reports require investigation. Childhood resources may delay the onset of ADHD.